Philosophy, art, and religion: understanding faith and creativity - Graham, Gordon (Cambridge studies in religion, philosophy, and society, 2017)
Religion, art, and the aesthetics of everyday life -- Sacred music -- Art, icon, and idolatry -- Literature and liturgy -- Glorious and transcendent places -- Re-thinking the sacred arts